Assessment of New E2 Protein Domain Interaction with PKR Protein to Control IFN Signaling - Dehghani, Behzad; Hashempour, Tayebeh; Musavi, Zahra; Hasanshahi, Zahra; Moayedi, Javad; Merat, Shahin (Current Proteomics, 2021)
Introduction: Controversy exists regarding the impact of Phosphorylation Homology Domain (PePHD) of Hepatitis C Virus (HCV) E2 protein on the interruption of the antiviral signaling pathway. A mechanism by which the virus evades the antiviral effect of interferon (IFN) alpha involves protein kinase (PKR) eukaryotic Initiation Factor 2 alpha (eIF2a) PePHD. By binding to PKR, PePHD inhibits its activity and, therefore, causes the virus to evade the antiviral activity of IFN. This study aimed to clarify the inconsistency of different conclusions reached in previous studies using reliable bioinformatics tools. Methods: Fifty-eight Iranian patients infected with HCV genotypes 1a and 3a and 58 healthy control individuals were examined. Plasma viral RNA was used to amplify and sequence the HCV E2 gene; also, HCV viral load, genotyping, IL-28B genotyping, alanine Aminotransferase (ALT), and aspartate aminotransferase (AST) test were determined. Bioinformatics tools determined the physicochemical properties, B-cell epitopes, post-modification changes, and secondary/tertiary structures, and also evaluated the interactions between E2 and PePHD regions. Results: The results showed a new domain that is responsible for binding to PKR protein and is important to the intrigued antiviral response. Physicochemical features and post-modifications were defined, showing that E2 is highly phosphorylated and there were numerous possible disulfide bonds. Secondary and tertiary structures for E2 protein were constructed. No significant relationship between ALT and AST and treatment failure was detected. Conclusion: Docking analysis showed a new domain in E2 protein that can be involved in the interaction between PKR and E2 protein. This finding may justify our results revealing the non-significant relationship between mutations in PePHD and treatment failure.
Keywords: PePHD